The Influence of Tanizaki’s Early Works on Edogawa Ranpo’s Novels - Bienati, Luisa (Annali di Ca’ Foscari: Serie Orientale, 2018)
From his debut in 1923, Edogawa Ranpo (1894-1965) acknowledged the influence of Tanizaki Jun’ichirō and often referred to his works. Tanizaki had published several short stories characterised by tantei shumi between 1911 and 1927, yet the link between the two authors lies not only in their choice of the narrative genre. Tanizaki was a great admirer of Edgar Allan Poe and translated many of his stories including “The Domain of Arnheim”. Ranpo, too, was overtly inspired by Poe’s stories “The Domain of Arnheim” and “Landor’s Cottage”, which can be seen in the plot and descriptions of Panoramatō kidan. The aim of my investigation is therefore to examine the path that leads us from Poe’s “The Domain of Arnheim”, to Tanizaki’s Konjiki no shi, and from Poe and Tanizaki to Ranpo’s Panoramatō kidan.